Mitochondrial Genome Sequence of the Legume Vicia faba - Negruk, Valentine (Frontiers in Plant Science, 2013)
The number of plant mitochondrial genomes sequenced exceeds two dozen. However, for a detailed comparative study of different phylogenetic branches more plant mitochondrial genomes should be sequenced. This article presents sequencing data and comparative analysis of mitochondrial DNA of the legume Vicia faba. The size of the V. faba circular mitochondrial master chromosome of cultivar Broad Windsor was estimated as 588,000bp with a genome complexity of 387,745bp and 52 conservative mitochondrial genes; 32 of them encoding proteins, three rRNA and 17 tRNA genes. Six tRNA genes were highly homologous to chloroplast genome sequences. In addition to the 52 conservative genes, 114 unique ORFs were found, 36 without significant homology to any known proteins and 29 with homology to the Medicago truncatula nuclear genome and to other plant mitochondrial ORFs, 49 ORFs were not homologous to M. truncatula but possessed sequences with significant homology to other plant mitochondrial or nuclear ORFs. In general, the unique ORFs revealed very low homology to known closely related legumes, but several sequence homologies were found between V. faba, Beta vulgaris, Nicotiana tabacum, Vitis vinifera and even the monocots Oryza sativa and Zea mays. Most likely these ORFs arose independently during angiosperm evolution (Kubo and Mikami, 2007; Kubo and Newton, 2008). Computational analysis revealed in total about 45% of V. faba mtDNA sequence being homologous to the Medicago truncatula nuclear genome (more than to any sequenced plant mitochondrial genome), and 35% of this homology ranging from a few dozen to 12,806 bp are located on chromosome 1. Apparently, mitochondrial rrn5, rrn18, rps10, ATP synthase subunit alpha, cox2 and tRNA sequences are part of transcribed nuclear mosaic ORFs.